Lipid and fatty acid composition of microalgae used in Malaysian aquaculture as live food for the early stage of penaeid larvae - Shamsudin, Lokman (Springer, 1992)
The total ash, chlorophyll, phaeopigment, lipid and fatty acid contents of three microalgae (the diatoms Chaetoceros calcitrans, Skeletonema costatum and the prymnesiophyte Isochrysis galbana) used in tropical Malaysian penaeid mariculture were studied. The axenic laboratory cultures were grown in f-2 medium, while outdoor cultures were grown in a commercial medium designed for optimum nutrition in tropical outdoor aquaculture operations. Considerable amounts (3-9% of the total fatty acid) of the polyunsaturated fatty acid 20:5w3 (eicosapentaenoic acid) were present in the diatoms; very small amounts were also found in I. galbana. Lipid contents were three to five times higher than chlorophyll a. There was an increase with culture age in the relative proportion of total C18 and C20 fatty acid components. The algae contained the w3-polyunsaturated fatty acids (PUFA) necessary for the growth and survival rate of the prawn larvae. However, only Chaetoceros calcitrans grew well under the conditions of temperature and salinity in the hatchery.